ANALISIS KINERJA KEUANGAN PAJAK DAERAH MENGGUNAKAN METODE VALUE FOR MONEY - Putri, Cyntia Johannes; Wahyuning Astuti, Sri WIbawani (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2021)
This study aims to determine how the level of economy, effectiveness, and efficiency of local tax financial performance in Ponorogo Regency. The object of this research is Ponorogo Regency. This research uses a descriptive method. Data collection techniques through documentation which can be done by re-recording, photographing, photocopying or buying. The type of data used is in the form of government published financial reports, namely local tax revenue reports and Ponorogo Regency regional income budget data. The results showed that the financial performance of local taxes measured using economic ratios was in the economic category, the efficiency ratio was in the very efficient category. The results of the effectiveness ratio show that the financial performance of local taxes is very effective.